POST “ARAB SPRING” SAUDI ARABIA: INTERNAL POLITICAL PROCESS AND POSSIBLE REFORMS - N. A. Gasymov (Сравнительная политика, 2015)
This article attempts to systematize analytical information on the “Arab Spring” in the Kingdom of Saudi Arabia. The author specifies causes of the public outcry, goals of the opposition groups along with the consequences of the “Arab Spring” for domestic politics.